Predicting teacher turnover in private universities: a machine learning approach based on 10 years of data and satisfaction factors - Jingwen, Wang; Yi, Liu; Xiaohong, Yang (Frontiers in Psychology, 2025)
BackgroundTeacher turnover poses a significant challenge to the sustainable development of private universities in China. While machine learning (ML) has been increasingly applied to turnover prediction, existing studies often overlook psychological factors and lack longitudinal analysis.MethodsThis study integrates a 10-year longitudinal dataset with satisfaction surveys from a private university in Western China. Exploratory Factor Analysis (EFA) was employed to extract key dimensions influencing turnover. Three ML models—K-Nearest Neighbors (KNN), Naive Bayes (NB), and Backpropagation Neural Network (BPNN)—were constructed and evaluated using accuracy, F1-score, and AUC.ResultsThe KNN model achieved the highest predictive performance (accuracy = 83.64%, F1 = 84.16%, AUC = 0.901). The “Compensation, Benefits, and Development” dimension was identified as the most influential factor, accounting for 25.41% of the variance.ConclusionThis study proposes an “EFA + ML” hybrid approach that enhances feature interpretability and prediction robustness, offering practical insights for human resource management in private higher education institutions.